(untitled) (Edad Media. Revista de Historia, 2017)
This article deals with the medieval history of the urban archives of the city of Montpellier. In a first part, it offers the long history of these collections by tracing the important moments in the transmission and transformation of medieval documentation produced within the institutional framework of the Consulate established in 1204-1205. In a second part, the article examines the transformations that affected urban archival memory from the beginning of the thirteenth to the mid-fourteenth century and links these to changes in methods of governing the urban universitas. Two periods are singled out: the first spans through the 1250s and 1260s and is a first move towards the empowerment of the urban administrative sphere, with the compilation of landmark books and the turning of a part of the city’s archives into a Treasury. The second period runs through the mid-fourteenth century, when a thorough reorganization of the classification system of the archivum that will facilitate the consultation of documents takes place, as does an unprecedented increase in the control exercised by urban administrations over the production and conservation of urban records.